1984
DOI: 10.1002/gepi.1370010406
|View full text |Cite
|
Sign up to set email alerts
|

The Cincinnati lipid research clinic family study: Analysis of commingling and family resemblance for fasting blood glucose

Abstract: Our specific aim in this study was to investigate commingling and family resemblance for fasting blood glucose in 160 randomly selected white families from the Princeton School District Lipid Research Clinics Family Study. Adjustment of fasting blood glucose for the influence of age, sex, and the use of oral contraceptives and construction of indices were performed simultaneously using multiple regression methods. Path analysis was carried out, constructing an environmental index based on special diet usage, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

1986
1986
2003
2003

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…shared family environment) and several studies have suggested that the familial resemblance in glucose levels is predominantly cultural [48,52,53]. However, in two studies of Caucasian pedigrees, polygenic effects were more pronounced [50,51]. POINTER does not permit discrimination of polygenic and transmitted environmental influences: evidence for intergenerational differences in the heritability of the multifactorial component (i.e.z ~ 1) may be taken to indicate support for additional sharing of environment between siblings but in practise the interpretation of z presents difficulties.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…shared family environment) and several studies have suggested that the familial resemblance in glucose levels is predominantly cultural [48,52,53]. However, in two studies of Caucasian pedigrees, polygenic effects were more pronounced [50,51]. POINTER does not permit discrimination of polygenic and transmitted environmental influences: evidence for intergenerational differences in the heritability of the multifactorial component (i.e.z ~ 1) may be taken to indicate support for additional sharing of environment between siblings but in practise the interpretation of z presents difficulties.…”
Section: Discussionmentioning
confidence: 98%
“…Serjeantson and Zimmet [46] used POINTER to adduce evidence for an autosomal dominant gene operating on a multifactorial background in Nauruan families. In contrast, segregation studies in populations at lower risk of diabetes (Japanese [47,48] and Caucasians [49,50]) have not found clear evidence for major gene effects,…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…been in the range between 0 to 39% [1,2,3], whereas the estimates for indices of insulin secretion and insulin sensitivity have been somewhat higher, 28 to 65% [4,5]. Segregation analyses have provided evidence for a major gene effect on both fasting and 1-h insulin [6].…”
mentioning
confidence: 99%
“…The only previous reports of path anal ysis of glucose tolerance were with respect to fasting plasma glucose concentration, in Japanese Americans in Hawaii [8] and Caucasians at the Cincinnati Lipid Re search Center (LRC) [9].…”
Section: Discussionmentioning
confidence: 99%